Picturebooks and reader training in the 21st century. An ecocritical reading of canonical works of children’s literature - Laliena, Daniel; Tabernero Sala, Rosa (Frontiers in Education, 2023)
The recent proliferation of environmental children’s literature and the growing interest in this type of books by researchers and proponents of ecocriticism could be deemed a byproduct of contemporary concerns regarding environmental sustainability. Considering books for children as more than mere tools for environmental awareness-raising prompts an approach to canonical picturebooks that reveals their ecocritical nature based on the esthetic, multimodal and literary dimensions of these works. This study proposes the analysis of 25 picturebooks by five influential female authors to identify the keys to their ecocritical reading. Indeed, the elements that define literary discourse construction in children’s books (paratextuality, illustration and design, character development and focalization) are precisely those that have proved to be fundamental in this sense. Interpreting these seminal works from an ecocritical vantage point updates them in step with current ecocentric paradigms by promoting a sense of wonder in young readers that leads them to delight in and reflect on nature and the environment.